Active trunk movement assessment as a key factor in wheelchair basketball classification - an original study - Marszalek, J.; Molik, B. (Acta Kinesiologica, 2021)
In wheelchair basketball the observation of active trunk movement during a game is done by a qualified panel of classifiers.Playersare allocated into one out of eight class.In the past, the map of the volume of action for each class player was created based on classifiers` experience and knowledge(in qualitative way, without the range of trunk movement). Based on Paralympics` classification standards there is a need to provide quantitative data for the current classes. The aim of this study was to create the map and reference values of the volume of trunk action of wheelchair basketball players and to check if there are differences in results between players representing different functional classes. The second aim was to investigate if there are significant benefits of using additional equipment with the sport wheelchair like sports straps that help players to achieve the greater volume of trunk action. Sixty-eight players divided into functional classes were asked to perform the maximum active trunk range of movement in three planes, in a sport wheelchair with straps and without straps, that was measured by the Kinect for Windows V2 sensor. The differences in movement was assessed by the t-test or the Wilcoxon test, differences between classes were done by ANOVA and the post hoc Tukey test. The discriminant analysis was calculated. Significant greater volume of trunk action in each plane was noticed in a sport wheelchair withstraps (p < .05). There were observed significant differences in trunk movement in three planes between neighboring classes (p < .05). 76.9% original grouped cases were correctly classified. The accuracy of the current classification system in wheelchair basketball was confirmed. Themap and reference values of the volume of trunk action will be helpful for all wheelchair basketball stakeholders. Trunk flexion and rotation discriminate the most effectively players. All class players should use appropriately fitted straps around hips during wheelchair basketball game, for safeness and wider volume of action.